Effect of pre-drying storage and drying method on the quality of dried kelp - Jonas Steenholdt Sparvath; Aurora Luiza Cardoso; Turid Rustad; Nikoline Ziemer; Lisbeth Truelstrup Hansen (Food Research International, 2025)

Management of Atlantic Bluefin Tuna (Thunnus thynnus) By-Products in Malta: Logistics, Biomass Quality and Environmental Impact - Giovanni Marco Cusimano; Clara A. Revue; Jui-Che Chiang; Turid Rustad; Abhilash Sasidharan; Paw Dalgaard; Laura Gasco; Francesco Gai; Ann-Dorit Moltke Sørensen; Eugenio Geremia; Gaetana Napolitano; Simona Paolacci (Journal of Cleaner Production, 2025)

The effects of freezing and thawing on Alaria esculenta - Randi Sund; Turid Rustad; Arne Duinker; Dagbjørn Skipnes (Journal of Applied Phycology, 2024)
Seaweeds must be stabilised shortly after harvesting to avoid rapid deterioration. To handle large amounts harvested during a short period, freezing and frozen storage until utilisation or further processing is one of the methods used industrially. The aim of this study was to assess the effects of different freezing and thawing procedures on Alaria esculenta by analysis of the chemical composition of the seaweed and the drip loss expelled during thawing. Thawing of industrially frozen A. esculenta resulted in a drip loss of 57% of wet weight. The drip loss had a dry matter content of 7% of wet weight, of which 71% was mineral content. Analysis showed that, of the dry matter excluding ash, alanine, aspartic acid, and mannitol were the main components lost to the drip loss. Experiments with a second batch of A. esculenta looking at quick and slow freezing and thawing showed that quick freezing resulted in a significantly lower drip loss than slow freezing; 20% compared to up to 42% of wet weight. Dry matter and mineral content of the drip loss of these samples were all around 6% of wet weight and 31% of dry weight. For some applications it might be of interest to reduce the concentration of potentially toxic elements such as iodine and heavy metals, but due to a high loss of other biomass this was not very effectively done by freezing and thawing. For preservation purposes, quick freezing is the best alternative to retain seaweed biomass.

Changes in food quality attributes of Saccharina latissima following pre-treatments, frozen storage and subsequent thawing - Pierrick Stévant; Finn Lillelund Aachmann; Øystein Arlov; Tom Ståle Nordtvedt; Antonio Sarno; Olav Andreas Aarstad; Leesa Jane Klau; Turid Rustad; Maren Sæther; Céline Rebours (Algal Research, 2024)

Variations in the chemical composition of Norwegian cultivated brown algae Saccharina latissima and Alaria esculenta based on deployment and harvest times - Øystein Arlov; Katharina Nøkling-Eide; Olav Andreas Aarstad; Synnøve Strand Jacobsen; Anne-Mari Langeng; Ana R. Borrero-Santiago; Maren Sæther; Turid Rustad; Finn Lillelund Aachmann; Håvard Sletta (Algal Research, 2024)

Heterotrophic growth of Galdieria sulphuraria on residues from aquaculture and fish processing industries - Daniel Pleissner; Stephanie Schönfelder; Nicole Händel; Julia Dalichow; Judith Ettinger; Kristine Kvangarsnes; Egidijus Dauksas; Turid Rustad; Janna Cropotova (Bioresource Technology, 2023)

Tuna sidestream valorization: a circular blue bioeconomy approach - Abhilash Sasidharan; Turid Rustad; Giovanni M. Cusimano (Environmental Science and Pollution Research, 2023)
Tuna is an economically significant seafood, harvested throughout the world, and is heavily traded due to its high nutritional quality and consumer acceptance. Tuna meat is rich in essential nutrients such as amino acids, polyunsaturated fatty acids (PUFA), and trace minerals. The huge volume of solid and liquid sidestreams generated during the processing stages of tuna is creating environmental and socioeconomic challenges in coastal areas. Different products such as fish meal, protein hydrolysates, collagen, enzymes, oil, and bone powder can be produced from tuna sidestreams. Using different nutrient recovery technologies like enzymatic hydrolysis, chemical processing, and green technologies, various categories of product value chains can be created in line with the conventional processing industry. This review attempts to provide a route map for the tuna industry for achieving the circular blue-bioeconomic objectives and reorient the irregular utilization pattern into a sustainable and inclusive path.

Trends in food emulsion technology: Pickering, nano-, and double emulsions - Gisle Øye; Sébastien Simon; Turid Rustad; Kristofer Paso (Current Opinion in Food Science, 2023)

Effect of Rosemary on Stabilization of Proteins during Frozen Storage of Mackerel ( Scomber scombrus ) - Kristine Kvangarsnes; Turid Rustad; Trygg Barnung; Wenche Emblem Larssen; Grete Hansen Aas (Journal of Aquatic Food Product Technology, 2021)

The Influence of Cooking Parameters and Chilled Storage Time on Quality of Sous-Vide Atlantic Mackerel ( Scomber scombrus ) - Janna Cropotova; Revilija Mozuraityte; Inger Beate Standal; Turid Rustad (Journal of Aquatic Food Product Technology, 2019)

Effects of drying on the nutrient content and physico-chemical and sensory characteristics of the edible kelp Saccharina latissima - Pierrick Stévant; Erlend Indergård; Aðalheiður Ólafsdóttir; Hélène Marfaing; Wenche Emblem Larssen; Joël Fleurence; Michael Y. Roleda; Turid Rustad; Rasa Slizyte; Tom Ståle Nordtvedt (Journal of Applied Phycology, 2018)

Biomass soaking treatments to reduce potentially undesirable compounds in the edible seaweeds sugar kelp (Saccharina latissima) and winged kelp (Alaria esculenta) and health risk estimation for human consumption - Pierrick Stévant; Hélène Marfaing; Arne Duinker; Joël Fleurence; Turid Rustad; Ingrid Sandbakken; Annelise Chapman (Journal of Applied Phycology, 2018)

Quality of Filleted Atlantic Mackerel ( Scomber Scombrus ) During Chilled and Frozen Storage: Changes in Lipids, Vitamin D, Proteins, and Small Metabolites, including Biogenic Amines - Inger Beate Standal; Revilija Mozuraityte; Turid Rustad; Leili Alinasabhematabadi; Nils-Gunnar Carlsson; Ingrid Undeland (Journal of Aquatic Food Product Technology, 2018)

Nutritional value of the kelps Alaria esculenta and Saccharina latissima and effects of short-term storage on biomass quality - Pierrick Stévant; Hélène Marfaing; Turid Rustad; Ingrid Sandbakken; Joël Fleurence; Annelise Chapman (Journal of Applied Phycology, 2017)

Muscle Quality and Proteolytic Enzymes of Farmed Atlantic Cod ( Gadus morhua ) During Storage: Effects of Pre-Slaughter Handling and Increased Storage Temperature - Lisbeth Hultmann; Torbjørn Tobiassen; Øyvind Aas-Hansen; Tran Minh Phu; Turid Rustad (Journal of Aquatic Food Product Technology, 2016)

Reduction of Salt in Haddock Mince: Effect of Different Salts on the Solubility of Proteins - Irina Viktorovna Andreetta-Gorelkina; Kirsti Greiff; Turid Rustad; Ida Grong Aursand (Journal of Aquatic Food Product Technology, 2016)

Bleeding of Farmed Atlantic Cod: Residual Blood, Color, and Quality Attributes of Pre- and Postrigor Fillets as Affected by Perimortem Stress and Different Bleeding Methods - Hanne Digre; Ulf Erikson; Ekrem Misimi; Inger Beate Standal; Lorena Gallart-Jornet; Siriporn Riebroy; Turid Rustad (Journal of Aquatic Food Product Technology, 2011)